Transverse spin forces and non-equilibrium particle dynamics in a circularly polarized vacuum optical trap. Issue 1 (December 2018) - Svak, V.; Brzobohatý, O.; Šiler, M.; Jákl, P.; Kaňka, J.; Zemánek, P.; Simpson, S.
Abstract We provide a vivid demonstration of the mechanical effect of transverse spin momentum in an optical beam in free space. This component of the Poynting momentum was previously thought to be virtual, and unmeasurable. Here, its effect is revealed in the inertial motion of a probe particle in a circularly polarized Gaussian trap, in vacuum. Transverse spin forces combine with thermal fluctuations to induce a striking range of non-equilibrium phenomena. With increasing beam power we observe (i) growing departures from energy equipartition, (ii) the formation of coherent, thermally excited orbits and, ultimately, (iii) the ejection of the particle from the trap. As well as corroborating existing measurements of spin momentum, our results reveal its dynamic effect. We show how the under-damped motion of probe particles in structured light fields can expose the nature and morphology of optical momentum flows, and provide a testbed for elementary non-equilibrium statistical mechanics. Here, the authors provide a vivid demonstration of the dynamic effect of transverse spin momentum in an optical beam in free space revealed by placing a dielectric bead in a counter-propagating optical beam trap in vacuum.